Controlled compression, amplification and frequency up-conversion of optical pulses by media with time-dependent refractive index - Löhr Alexander Gabriel; Ivanov Misha Yu; Khokhlova Margarita A. (Nanophotonics)
Control over the time dependence of the refractive index of a material allows one to modify and manipulate the properties of light propagating through it. While metamaterials provide a promising avenue in this context, another route has been extensively explored by the ultrafast community — the so-called molecular modulators. Indeed, impulsively-aligned diatomic molecules provide a unique medium, where periodic rotational revivals induced by a pump pulse persist for tens of picoseconds, offering an excellent opportunity for the controlled modification of the refractive index and, therefore, of femtosecond laser pulses propagating through these media. Here we present an analytical theory which describes this process and stumble across a novel mechanism revealing exponential transformations of the probe pulse — its compression, amplification and frequency up-conversion. In particular, our analytical results predict the generation of amplified ultrashort (about 20 fs) ultraviolet pulses centered around 550 nm, starting with near infrared input pulses centered on 1 μm of about 30 fs duration, under very realistic experimental conditions.